The Twilight Zone of Political Transition: Between Revolution and Democratic Change - Marsili, M. (Political Reflection Magazine, 2019)
O´Donnell, Schmitter and Whitehead define transition broadly as "the interval between one political regime and another". Plattner concludes that "they emphasize a particular path to democratic transition – one that is neither violent nor revolutionary, but proceeds from negotiation between an outgoing authoritarian regime and its democratic opposition and often relies upon formal pacts that provide security guarantees to both sides". I wonder whether there is a common and clear pattern to democratic transition, or if rather exists a "twilight zone" in which violence is still permitted as the "vestige" of the vanishing authoritarian regime. In this brief article, I explore the connections between revolution and democracy in political changes.